FT-IR study of montmorillonite–chitosan nanocomposite materials - Paluszkiewicz, C.; Stodolak, E.; Hasik, M.; Blazewicz, M. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2011)
Bone defect is one of the most frequent problems in bone tissue reconstruction in which application of a biomaterial filling is necessary. It creates a still rising demand of biomaterials for bone surgery. Polymer–ceramic nanocomposites (e.g. based on chitosan matrix) is a group of novel materials whose properties such as strength, Young's modulus, bioactivity and controlled degradation time make them suitable materials for filling bone defects. Investigations of nanocomposite foils which consisted of biopolymer–chitosan (CS) matrix and montmorillonite (MMT) as a nano-filler was the subject of the work. The nanocomposite materials were produced by a two-step dispersion of the nanoparticles in the biopolymer matrix. The first stage involved mechanical stirring and the second one – ultrasonic agitation. Mechanical tests were performed on the nanocomposites and their Young's modulus was estimated. Significant improvement of mechanical properties of the nanocomposites in comparison with the pure polymer (CS) was observed. The nanocomposite foils (CS/MMT) were subjected to FT-IR spectroscopy investigations whose objective was to explain the reason of the change in mechanical characteristics of the nanocomposites. Transmission and ATR techniques operating in MIR range were used to study the nanocomposites. The FT-IR techniques were used to determine interactions at nanoparticle–biopolymer matrix interface. A pure unmodified CS foil was used as a reference material for FT-IR studies. It was proven that application of FT-IR techniques allows not only to identify phases, but also to explain structural changes in the systems studied.